2019
DOI: 10.24996/ijs.2019.60.12.7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of anemia among children infected with Entamoeba histolytica in Baghdad

Abstract: The relation between Entamoeba histolytica and anemia has lately had much attention. The aim of this study was to determine the possible correlation between anemia and parasitic intestinal infection with E.histolytica in children from Baghdad-Iraq. This study was conducted from October 2018 to April 2019 in different hospitals, primary health care centers, and primary schools. Eighty-one children participated in this study and their ages were between 1 and 12 years. The participants were divided into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The transmission of this kind of diarrhea is increased by contaminated water and poor sanitation and hygiene (2) . It is known that many intestinal parasites are associated with infectious diarrhea especially in children (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of this kind of diarrhea is increased by contaminated water and poor sanitation and hygiene (2) . It is known that many intestinal parasites are associated with infectious diarrhea especially in children (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…In this study Similar study in Karbala 2021 indicted findings revealed that there was no relation between the type of anemia and age or gender [4] . And study in Bagdad indicted, the statistical analysis showed no significant relation between age and prevalence of anemia and no significant relation was noticed between gender with anemia [5]. Study in Tanzania indicate that younger children(under 2 years) were more likely to be anemia compared to their older peers [6].Anemia is major source of morbidity and mortality worldwide [7].…”
Section: -Discussionmentioning
confidence: 98%
“…• Hepcidin, Divalent Metal Ion Transporter-1 (DMT1), Total Iron Binding capacity, Ferro protein were measured using a PKL device (PPC POKLER ITALIA 230 Automatic ElISA Reader). 1-4: Physiological tests: 1-4-1: CBC complete blood count analysis 1 ml of blood samples obtained were immediately placed in EDTA anticoagulation tubes to measure hemoglobin and white blood cell concentrations and packed cell volume for both infected and unaffected children using an automatic CBC blood analyzer (Zeki and Harith, 2019). It was kept in a cool box and was sent within an hour to the laboratory for blood analysis using a Sysmex device.…”
Section: -Sample Collectionmentioning
confidence: 99%